β Common Receptor Mediates Erythropoietin-Conferred Protection on OxLDL-Induced Lipid Accumulation and Inflammation in Macrophages - Tzong-Shyuan Lee; Kuo-Yun Lu; Yuan-Bin Yu; Hsueh-Te Lee; Feng-Chuan Tsai (Mediators of Inflammation)
Erythropoietin (EPO), the key factor for erythropoiesis, also protects macrophage foam cells from lipid accumulation, yet the definitive mechanisms are not fully understood. β common receptor (βCR) plays a crucial role in the nonhematopoietic effects of EPO. In the current study, we investigated the role of βCR in EPO-mediated protection in macrophages against oxidized low-density lipoprotein- (oxLDL-) induced deregulation of lipid metabolism and inflammation. Here, we show that βCR expression was mainly in foamy macrophages of atherosclerotic aortas from apolipoprotein E-deficient mice. Results of confocal microscopy and immunoprecipitation analyses revealed that βCR was colocalized and interacted with EPO receptor (EPOR) in macrophages. Inhibition of βCR activation by neutralizing antibody or small interfering RNA (siRNA) abolished the EPO-conferred protection in oxLDL-induced lipid accumulation. Furthermore, EPO-promoted cholesterol efflux and upregulation of ATP-binding cassette (ABC) transporters ABCA1 and ABCG1 were prevented by pretreatment with βCR neutralizing antibody or βCR siRNA. Additionally, blockage of βCR abrogated the EPO-conferred anti-inflammatory action on oxLDL-induced production of macrophage inflammatory protein-2. Collectively, our findings suggest that βCR may play an important role in the beneficial effects of EPO against oxLDL-elicited dysfunction of macrophage foam cells.